Progression of cannabis withdrawal symptoms in people using medical cannabis for chronic pain. (6th January 2021) - Coughlin, Lara N.; Ilgen, Mark A.; Jannausch, Mary; Walton, Maureen A.; Bohnert, Kipling M.
Abstract: Background and aims: Research from cohorts of individuals with recreational cannabis use indicates that cannabis withdrawal symptoms are reported by more than 40% of those using regularly. Withdrawal symptoms are not well understood in those who use cannabis for medical purposes. Therefore, we prospectively examined the stability of withdrawal symptoms in individuals using cannabis to manage chronic pain. Design, Setting, Participants: Using latent class analysis (LCA) we examined baseline cannabis withdrawal to derive symptom profiles. Then, using latent transition analysis (LTA) we examined the longitudinal course of withdrawal symptoms across the time points. Exploratory analyses examined demographic and clinical characteristics predictive of withdrawal class and transitioning to more or fewer withdrawal symptoms over time. A cohort of 527 adults with chronic pain seeking medical cannabis certification or re‐certification was recruited between February 2014 and June 2015. Participants were recruited from medical cannabis clinic waiting rooms in Michigan, USA. Participants were predominantly white (82%) and 49% identified as male, with an average age of 45.6 years (standard deviation = 12.8). Measurements: Baseline, 12‐month and 24‐month assessments of withdrawal symptoms using the Marijuana Withdrawal Checklist–revised. Findings: A three‐class LCA model including a mild (41%), moderate (34%) and severe (25%) symptom class parsimoniously represented withdrawal symptoms experienced by people using medical cannabis. Stability of withdrawal symptoms using a three‐class LTA at 12 and 24 months ranged from 0.58 to 0.87, with the most stability in the mild withdrawal class. Younger age predicted greater severity and worsening of withdrawal over time. Conclusions: Adults with chronic pain seeking medical cannabis certification or re‐certification appear to experience mild to severe withdrawal symptoms. Withdrawal symptoms tend to be stable over a 2‐year period, but younger age is predictive of worse symptoms and of an escalating withdrawal trajectory.